Measuring Efficiency in Banks: A Brief Survey on Non – Parametric Technique (Data Envelopment Analysis) - Alrafadi, Khalad M. S; Yusuf, Mazila Md; Kamaruddin, Badrul Hisham (International Journal of Business, Economics and Management, 2016)
Objective: This paper provides a survey of efficiency in banks using Data Envelopment Analysis (DEA) in developed and developing countries. Methods: There are two ways were used; the first one is analyse previous reviews, and the other one is systemic search from ProQuest, Emerald, Scopus and Science Direct. The search conducted to identify efficiency in banks in developed and developing countries. Originality: This study contributes in the existing literature in measuring efficiency in banks using DEA as a non – parametric technique. Results: Studies that was survey showed that the score of allocative efficiency was more than technical and cost efficiencies. Also, Studies showed that the scores of cost efficiency were more than the scores of profit efficiency. Conclusion: This paper shows that most of these studies were conducted in developed countries context, Also many studies were in developing countries. But, very few studies were conducted in the context of banking industry in Arab countries.